[18F]Fluorophenylazocarboxylates: Design and Synthesis of Potential Radioligands for Dopamine D3 and μ‑Opioid Receptor. - Nebel, Natascha; Strauch, Brigitte; Maschauer, Simone; Lasch, Roman; Rampp, Hannelore; Fehler, Stefanie; Bock, Leonard; Hübner, Harald; Gmeiner, Peter; Heinrich, Markus; Prante, Olaf (ACS Omega, 2017)
18F-Labeled building blocks from the type of [18F]fluorophenylazocarboxylic-tert-butyl esters offer a rapid, mild, and reliable method for the 18F-fluoroarylation of biomolecules. Two series of azocarboxamides were synthesized as potential radioligands for dopamine D3 and the μ-opioid receptor, revealing compounds 3d and 3e with single-digit and sub-nanomolar affinity for the D3 receptor and compound 4c with only micromolar affinity for the μ-opioid receptor, but enhanced selectivity for the μ-subtype in comparison to the lead compound AH-7921. A "minimalist procedure" without the use of a cryptand and base for the preparation of 4-[18F]fluorophenylazocarboxylic-tert-butyl ester [ 18 F]2a was established, together with the radiosynthesis of methyl-, methoxy-, and phenyl-substituted derivatives ([ 18 F]2b-f). With the substituted [18F]fluorophenylazocarbylates in hand, two prototype azocarboxylates radioligands were synthesized by 18F-fluoroarylation, namely the methoxy azocarboxamide [ 18 F]3d as the D3 receptor radioligand and [ 18 F]4a as a prototype structure of the μ-opioid receptor radioligand. By introducing the new series of [18F]fluorophenylazocarboxylic-tert-butyl esters, the method of 18F-fluoroarylation was significantly expanded, thereby demonstrating the versatility of 18F-labeled phenylazocarboxylates for the design of potential radiotracers for positron emission tomography .
EVALuna2:34730

Exploring Structural Determinants of Bias among D4 Subtype-Selective Dopamine Receptor Agonists - Graßl, Fabian; Bock, Leonard; Huete-Huerta González, Álvaro; Schiller, Martin; Gmeiner, Peter; König, Jörg; Fromm, Martin; Hübner, Harald; Heinrich, Markus (Journal of Medicinal Chemistry, 2023)
The high affinity dopamine D4 receptor ligand APH199 and derivatives thereof exhibit bias toward the Gi signaling pathway over β-arrestin recruitment compared to quinpirole. Based on APH199, two novel groups of D4 subtype selective ligands were designed and evaluated, in which the original benzyl phenylsemicarbazide substructure was replaced by either a biphenylmethyl urea or a biphenyl urea moiety. Functional assays revealed a range of different bias profiles among the newly synthesized compounds, namely, with regard to efficacy, potency, and GRK2 dependency, in which bias factors range from 1 to over 300 and activation from 15% to over 98% compared to quinpirole. These observations demonstrate that within bias, an even more precise tuning toward a particular profile is possible, which─in a general sense─could become an important aspect in future drug development. Docking studies enabled further insight into the role of the ECL2 and the EPB in the emergence of bias, thereby taking advantage of the diversity of functionally selective D4 agonists now available.
CRIS-Team Scopus Importer:2023-08-11

Regioselective Radical Arylation of 3-Hydroxypyridines - Fürst, Michael; Bock, Leonard; Heinrich, Markus (Journal of Organic Chemistry, 2016)
The titanium(III)-mediated radical arylation of 3-hydroxypyridines was found to proceed with high regioselectivity for the 2-position. Using aryldiazonium chlorides, which were prepared from the corresponding anilines, as aryl radical sources, a range of 3-hydroxy-2-phenylpyridines were obtained in moderate to good yields under simple reaction conditions. Reactions of ortho-carboxylic ester substituted phenyldiazonium salts directly provided tricyclic benzopyranopyridinones.

Synthesis of 2-(Chlorodifluoromethyl)indoles for Nucleophilic Halogen Exchange with [18F]Fluoride - Bock, Leonard; Schultheiss, Stefanie K.; Maschauer, Simone; Lasch, Roman; Gradl, Susanne; Prante, Olaf; Zard, Samir Z.; Heinrich, Markus (European Journal of Organic Chemistry, 2021)
The synthesis of 2-[18F]trifluoromethylated indoles from the corresponding chlorodifluoromethyl precursors was found to proceed under milder conditions when compared to known metal-free nucleophilic exchange reactions with [18F]fluoride on chlorodifluoro-methyl arenes. A key element in the reaction course is – most likely – a favorable elimination-addition mechanism on the 2-methyl position of the indole. Given the increasing interest in 18F-labelled compounds, this single step labeling methodology nicely complements the so far existing routes to 2-[18F]trifluoromethylated indoles.
CRIS-Team Scopus Importer:2021-12-24
Keywords: Fluorine; Indoles; Nucleophilic substitution; Radical reactions; Radiochemistry